Advancements in DNA-based molecular markers to unravel the genetic diversity of endangered plants - Haque, Inamul (Current Botany, 2025)
One of the primary requirements to develop effective and practical sustainable management strategies for endangered plant species, is the assessment of genetic diversity. DNA-based molecular markers have proven themselves to be an excellent tool to assess many parameters including elucidation of genetic diversity for the past few decades. During this period, DNA-based marker technology has undergone many changes. From the initial RFLP to the contemporary systems that use high-throughput sequencing or next-generation sequencing platforms that have revolutionized genetic diversity assessment. This review focuses on the application of the molecular markers and, a few of their variants, to evaluate the genetic diversity of endangered plants along with their advantages, limitations as well as future prospects and scope.